2007
DOI: 10.1038/nrmicro1621
|View full text |Cite
|
Sign up to set email alerts
|

Current insights into the biology and pathogenesis of Pneumocystis pneumonia

Abstract: The fungal infection Pneumocystis pneumonia is the most prevalent opportunistic infection in patients with AIDS. Although the analysis of this opportunistic fungal pathogen has been hindered by the inability to isolate it in pure culture, the use of molecular techniques and genomic analysis have brought insights into its complex cell biology. Analysis of the intricate relationship between Pneumocystis and the host lung during infection has revealed that the attachment of Pneumocystis to the alveolar epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
184
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(195 citation statements)
references
References 140 publications
1
184
0
10
Order By: Relevance
“…However, studies of cultured lung epithelial cells have shown that the adherence of Pneumocystis alone does not disrupt the structure or barrier function of alveolar epithelial cells, although proliferative repair of the epithelium is reduced. It is therefore unlikely that the adherence of Pneumocystis to alveolar epithelium is by itself responsible for the diffuse alveolar damage in severe pneumonia (Benfield et al, 1997;Thomas & Limper, 2007). Rather, the inflammatory responses in the host are primarily responsible for the compromise of the alveolar-capillary surface (Thomas & Limper, 2007).…”
Section: Interactions Of Pneumocystis With Alveolar Host Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, studies of cultured lung epithelial cells have shown that the adherence of Pneumocystis alone does not disrupt the structure or barrier function of alveolar epithelial cells, although proliferative repair of the epithelium is reduced. It is therefore unlikely that the adherence of Pneumocystis to alveolar epithelium is by itself responsible for the diffuse alveolar damage in severe pneumonia (Benfield et al, 1997;Thomas & Limper, 2007). Rather, the inflammatory responses in the host are primarily responsible for the compromise of the alveolar-capillary surface (Thomas & Limper, 2007).…”
Section: Interactions Of Pneumocystis With Alveolar Host Cellsmentioning
confidence: 99%
“…In contrast, surfactant protein D mediates the aggregation of the Pneumocystis organisms, but because the aggregated organisms are extremely poorly taken up by macrophages, they may escape elimination. Pulmonary surfactant phospholipids, which contribute to the low surface tension in the alveoli, are reduced during PcP, and abnormalities in the composition and function of the surfactant are the result of the host's inflammatory response to Pneumocystis, rather than direct effects of the organisms on the surfactant components (Wright et al, 2001;Thomas & Limper, 2007).…”
Section: Interactions Of Pneumocystis With Alveolar Host Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Review article by Thomas and Limper on Pneumocystis pneumonia (PcP) published in Nature Reviews Microbiology illustrates the biological insights that have been gained from the use of molecular tools and the more recent technique of observation 1 . In this Correspondence, we discuss recent findings concerning the prevalence of trichomonads in the lungs of patients in different clinical contexts, including PcP.…”
mentioning
confidence: 99%